Evaluasi Kebijakan Ekonomi melalui Pendekatan Ekonometrika - Dwikhana Angelica; ⁠Rima Damayanti; Gustina Masitoh (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Economic policies are often designed with the expectation of improving macroeconomic stability and public welfare. However, without empirical evaluation, it is difficult to determine whether such policies achieve their intended outcomes. This study aims to examine how econometric approaches can be used to evaluate the effectiveness of economic policies in a more measurable and objective manner. The research adopts a quantitative approach using secondary data derived from official economic statistics. The analysis applies econometric models, particularly panel data regression and causal inference techniques, to assess the impact of selected policies on key economic indicators such as growth, inflation, and unemployment. The findings suggest that econometric methods provide a systematic framework to identify the magnitude and direction of policy impacts, while also revealing potential biases and limitations in policy implementation. Furthermore, the results highlight that not all policies produce uniform effects across regions and time, emphasizing the importance of context in economic decision-making. The study implies that policymakers should rely more on data-driven evaluation to improve policy design and effectiveness. By integrating econometric analysis into policy assessment, governments can enhance accountability and ensure that economic interventions are aligned with real-world conditions.